The most democratic branch : how the courts serve America - Rosen, Jeffrey, 1964- (Institutions of American democracy series., 2006)
Many critics attack federal judges as activists out of step with the mainstream of American thought. Others argue that judges should place principle before the views of the people. This book disagrees with both assertions, stating that contrary to what interest groups claim, the federal courts by and large reflect the opinions of the mainstream.